2022
DOI: 10.3390/ijerph19169996
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Evolution and Driving Factors of Urban Ecological Well-Being Performance in China

Abstract: Extensive development leads to the decline of ecological well-being, and it is necessary to improve the urban ecological well-being performance (EWP). This paper adopted the Super-slack-based measure (Super-SBM) model to evaluate the EWP of 285 Chinese prefecture level cities from 2011 to 2017. The exploratory spatial data analysis method (ESDA) was used to explore the spatial and temporal evolution characteristics of the EWP, and then the spatial Durbin model (SDM) was adopted to analyze the driving factors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 57 publications
(52 reference statements)
3
14
0
Order By: Relevance
“…It is concluded that the spatial distribution of the YREB’s EWP has obvious spillover effects, and its distribution shows “H-H” and “L-L” agglomeration features. This finding confirms the spatial distribution characteristics of EWP observed at the national scale by Bian et al [ 33 ], indicating a cross-scale similarity in spatial clustering of the EWP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is concluded that the spatial distribution of the YREB’s EWP has obvious spillover effects, and its distribution shows “H-H” and “L-L” agglomeration features. This finding confirms the spatial distribution characteristics of EWP observed at the national scale by Bian et al [ 33 ], indicating a cross-scale similarity in spatial clustering of the EWP.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the research on the influencing factors of EWP, scholars have mainly investigated the effects of economic growth, industrial structure, urbanization, technological progress, and foreign direct investment [ 33 ]. However, the knowledge about the role of causal factors in influencing EWP patterns remains to be limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, this paper uses environmental-pollution indicators as undesired outputs, and industrial wastewater, industrial waste gas, carbon emissions per capita, and industrial solid waste are chosen to characterize them. The accuracy of these indicators is confirmed by the studies of Xiao et al and Bian et al [27,43].…”
Section: Evaluation Index Systemsupporting
confidence: 52%
“…Therefore, modeling methods based on the multi-input-multi-output perspective were born, including the stochastic frontier approach (SFA) and data envelopment analysis (DEA) methods. For example, Xiao et [42,43]. However, the modeling approach has some drawbacks, such as multiple input and output indicators that may lead to problems in data acquisition and processing and limit its use to compare multiple countries and regions [36].…”
Section: Ecological Well-being Performancementioning
confidence: 99%
See 1 more Smart Citation